A common strangeness : contemporary poetry, cross-cultural encounter, comparative literature - Edmond, Jacob (New York : Fordham University Press, 2012)
"Why is our world still understood through binary oppositions-East and West, local and global, common and strange-that ought to have crumbled with the Berlin Wall? What might literary responses to the events that ushered in our era of globalization tell us about the rhetorical and historical underpinnings of these dichotomies? In A Common Strangeness, Jacob Edmond exemplifies a new, multilingual and multilateral approach to literary and cultural studies. He begins with the entrance of China into multinational capitalism and the appearance of the Parisian flaneur in the writings of a Chinese poet exiled in Auckland, New Zealand. Moving among poetic examples in Russian, Chinese, and English, he then traces a series of encounters shaped by economic and geopolitical events from the Cultural Revolution, perestroika, and the June 4 massacre to the collapse of the Soviet Union, September 11, and the invasion of Iraq. In these encounters, Edmond tracks a shared concern with strangeness through which poets contested old binary oppositions as they reemerged in new, post-Cold War forms."--Project Muse
Yang Lian and the Flâneur in exile -- Arkadii Dragomoshchenko and poetic correspondences -- Lyn Hejinian and Russian estrangement -- Bei Dao and world literature -- Dmitri Prigov and cross-cultural conceptualism -- Charles Bernstein and broken English.
Includes bibliographical references (pages 235-264) and index.
Print version record.
JSTOR
Keywords: Poetry, Modern -- 20th century -- History and criticism; Comparative literature; Literature and globalization; Littérature et mondialisation; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Comparative literature; Literature and globalization; Poetry, Modern; 1900-1999; Electronic books; poetry; Criticism, interpretation, etc; Poetry; Poésie.